2015
DOI: 10.1021/ja511250m
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium-Catalyzed Desymmetrization of Aminodialkenes and Aminodialkynes through Enantioselective Hydroamination

Abstract: The catalytic addition of alkenes and amines (hydroamination) typically provides α-or β-amino stereocenters directly through C-N or C-H bond formation. Alternatively, desymmetrization reactions of symmetrical aminodialkenes or aminodialkynes provide access to stereogenic centers with the position controlled by the substrate's structure. In the present study of an enantioselective zirconium-catalyzed hydroamination, stereocenters resulting from C-N bond formation and desymmetrization of a prochiral quaternary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…For example, we recently reported that substrate concentration affected the cis:trans ratio in an enantioselective Zr-catalyzed monocyclization reaction of aminodialkenes and aminodialkynes to give optically active pyrrolidines. 45 In addition, Marks and co-workers showed in their seminal study that diastereoselectivity in Cp* 2 LaCH(SiMe 3 ) 2 -catalyzed hydroaminations of chiral aminoalkenes is also influenced by concentration. 46 Rare-earth compounds and a few zirconium catalysts give hydroamination/bicyclization products through a two-step process in which the second cyclization requires conditions more forcing than those in the first.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, we recently reported that substrate concentration affected the cis:trans ratio in an enantioselective Zr-catalyzed monocyclization reaction of aminodialkenes and aminodialkynes to give optically active pyrrolidines. 45 In addition, Marks and co-workers showed in their seminal study that diastereoselectivity in Cp* 2 LaCH(SiMe 3 ) 2 -catalyzed hydroaminations of chiral aminoalkenes is also influenced by concentration. 46 Rare-earth compounds and a few zirconium catalysts give hydroamination/bicyclization products through a two-step process in which the second cyclization requires conditions more forcing than those in the first.…”
Section: ■ Introductionmentioning
confidence: 99%
“…26 In the case of amino dialkenes ( 58a–58g ), two stereocenters are formed in the reaction, one through the desymmetrization of a quaternary center and the other through C–N bond formation. By varying reaction conditions the authors were able to achieve reasonable diastereocontrol.…”
Section: Organometallicmentioning
confidence: 99%
“…The latter are neglected in MF treatments. The second phenomenon involves reactions with concentration-dependent selectivity, and specifically stereoselectivity where the product B can have distinct cis (B c ) and trans (B t ) forms [15]. Here, the selection of the B c or B t product is controlled by the concentration of the reactant, A.…”
Section: Introductionmentioning
confidence: 99%
“…However, here we first provide some brief comments for broader background and motivation regarding the type of systems falling into the above class and also on theoretical methodologies with the potential to provide a firstprinciples characterization of reaction kinetics. With regard to concentration-dependent selectivity, homogeneous catalytic desymmetrization of diallylamines to give diastereomers (using a Zr-centered catalyst) exhibits a quite strong variation with reactant concentration of cis to trans selectivity [15]. Specifically, the yield of trans relative to cis product increases with reactant concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation